EFEKTIVITAS PELAYANAN IZIN USAHA PERDAGANGAN DI DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU (DPMPTSP) KOTA SURAKARTA - Tri Widiarti; Liliek Winarni; Joko Suranto (Solidaritas: Jurnal Ilmu-Ilmu Sosial, 2020)
The One Stop Integrated Investment and Services Office (DPMPTSP) is a public organization that organizes public services, one of which is the service of trading business licenses. The problem with licensing services for trade business licenses in the city of Surakarta is that there are still many business actors who do not understand the one-stop online licensing system (OSS) due to lack of knowledge about the use of internet-based technology. Effectiveness is a benchmark for an organization in achieving its predetermined goals. To measure the effectiveness of trade business permit services in DPMPTSPSurakarta City uses a process approach according to Lubis and Martani Huseini which consists of 5 indicators namely service efficiency, service procedures, employee responsiveness, coordination between leaders and subordinates, and facilities and infrastructure. This research uses a descriptive method with a qualitative approach, with data collection used are interviews, documentation and observation. The technique of determining the informants in this study uses purposive sampling. Data analysis techniques used, namely data condensation, data presentation, and conclusions. The results of this study indicate that the trade business permit services carried out by the DPMPTSPSurakarta City are quite effective. However, the responsiveness of employees in the responsiveness of employees to complaints from public must be increased even more, so that people do not feel employees in serving convoluted and confusing. The condition of infrastructure needs improvement because it also supports the comfort of the public. Keywords: Effectiveness, Service, Business Permit